L2 control of LPV systems with saturating actuators: Polya approach - Delibasi, Akin; Kucukdemiral, Ibrahim B.; Cansever, Galip (WILEY, 2013)
This paper addresses the design problem of L2, gain-scheduling non-linear state-feedback controller for linear parameter varying (LPV) systems, subjected to actuator saturations and bounded energy disturbances, by using parameter-dependent type Lyapunov functions. The paper provides a systematic procedure to generate a sequence of linear matrix inequality (LMI) type conditions of increasing precision for obtaining a suboptimal L2 state-feedback controller. The presented method utilizes the modified sector condition for formalization of actuator saturation and homogeneous polynomial parameter-dependent representation of LPV systems. Both simulations and experimental studies on an inverted pendulum on a cart system illustrate the benefits of the approach. Copyright (C) 2011 John Wiley & Sons, Ltd.
Keywords: homogeneous polynomial parameter-dependent Lyapunov functions; input to state stability; LMIs; actuator saturation; inverted pendulum; real-time control; DEPENDENT LYAPUNOV FUNCTIONS; GUARANTEED COST COMPUTATION; UNCERTAIN LINEAR-SYSTEMS; STABILITY; SUBJECT; OPTIMIZATION; DESIGN; H-2; Automation & Control Systems; Operations Research & Management Science; Mathematics